Site-Specific Traffic Management Improvement by Implementing Human Performance Analysis to Eliminate Potential Serious Injury and Fatality (The Indonesian Journal of Business Administration, 2020)
PT CVD placed the highest priority on the health and safety workforce and protection of the company's assets, communities, and the environment. Health and safety of the workforce is become a core value of PT CVD. Starting 2018, PT CVD introduced Human Performance concepts as one of many tools to eliminate Serious Injury and Fatality in operations. PT CVD believes that Human, Culture, Work systems, Equipment and Processes are bound and interacts as a system that is interrelated and influential to each other. Human Performance is a field of study related to process improvement methodologies which focus on improving performance at societal, organizational, process and individual performer levels to improve work productivity and efficiency which is based on developing systematic systems. Currently PT CVD manages more than 50 remediation sites and deals with more than 500 heavy equipment and heavy vehicle managed by business partners. PT CVD requires each active work site to design, develop, manage and also communicate a safe driving environment by implementing Site-Specific Traffic Management Plan to support the operation safely. However, we experienced some serious near miss events in the remediation activities. And based on field observation, the safety and compliance performance related to the Site-Specific Traffic Management Plan implementation are still below 100% conformance due to noncompliance Site-specific traffic plan, inadequate PPE, inadequate traffic management sign, inadequate pedestrian pathway inside working area and so on. It means the hazard associated within the working is still not well mitigated yet, especially for vehicle-human interface activities. Based on the business situation analysis, the project team decided to identify the root cause of the problem by using Human Performance Analysis thru Performance Mode and Error Traps identifications. Those tools helps project team to dig deeper into the main issues, and also analyze the problems in the comprehensive view by optimizing Human Performance components (People, Culture, Work System, Equipment and Processes) to define the proper corrective actions in order to improve safety performance and compliance and eliminate potential serious injury and fatality.According to the analysis, the root cause of the issues is 40% of PMCoW have inadequate competency and capability related to SSTMP procedure, lack of Contractor’s Project Management commitment, lack of operational management control, inadequate understanding of SSTMP procedure by field personnel and lack of sense of vulnerability. The improvement actions have been implemented and successfully improve site-specific traffic management safety performance and compliance from 79 to 100% and eliminate potential risk to serious injury and fatality in PT CVD remediation project.Keywords: safety and compliance, human performance, site-specific traffic management, serious injury and fatality